Bonjour,
Résoudre les équations:
a.
(3x + 1)(x - 9) = 0
- Équation produit nul : Un produit est nul si et seulement si au moins un de ses facteurs est nul.
>> Soit 3x + 1 = 0
3x = -1
x = -1/3
>> Soit x - 9 = 0
x = 9
S={ -1/3 ; 9 } ✅
b.
(6x + 7)(4x - 11) = 0
- Équation produit nul : Un produit est nul si et seulement si au moins un de ses facteurs est nul.
>> Soit 6x + 7 = 0
6x = -7
x = -7/6
>> Soit 4x - 11 = 0
4x = 11
x = 11/4 = 2,75
S={ -7/6 ; 2,75 } ✅
c.
(9x - 3)(-5x - 13) = 0
- Équation produit nul : Un produit est nul si et seulement si au moins un de ses facteurs est nul.
>> Soit 9x - 3 = 0
9x = 3
x = 3/9 = 1/3
>> Soit -5x - 13 = 0
-5x = 13
5x = -13
x = -13/5 = -2,6
S={ -2,6 ; 1/3 } ✅
Bonne journée